Secure communicating systems : - Huth, Michael (Cambridge University Press, 2001)
This volume details what every computer scientist ought to know about cryptographic systems, security protocols, and secure information flow in programs. Highlights include discussions of the new advanced encryption standard "Rijndael"; an optimal public-key encryption using RSA which turns "textbook RSA" into a practical implementation; standard security models for information flow in computer programs or human organizations; and moral, legal, and political issues.